2011
DOI: 10.1152/ajpgi.00308.2011
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin uptake by pancreatic acinar cells: effect of chronic alcohol feeding/exposure

Abstract: Thiamin is important for normal function of pancreatic acinar cells, but little is known about its mechanism of uptake and about the effect of chronic alcohol use on the process. We addressed these issues using freshly isolated rat primary and rat-derived cultured AR42J pancreatic acinar cells as models. Results showed thiamin uptake by both primary and cultured AR42J pancreatic acinar cells to be via a specific carrier-mediated mechanism and that both of the thiamin transporters 1 and 2 (THTR-1 and THTR-2) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 28 publications
(44 reference statements)
2
49
0
Order By: Relevance
“…Whole cell lysate prepared from primary mouse PAC and 266-6 cells chronically fed/exposed to alcohol and their respective controls were used for Western blot analysis as described previously (44,47). The cells were suspended in 200 l of RIPA buffer (Sigma) according to manufacturer's protocol and supplemented with protease inhibitor cocktail (Roche).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole cell lysate prepared from primary mouse PAC and 266-6 cells chronically fed/exposed to alcohol and their respective controls were used for Western blot analysis as described previously (44,47). The cells were suspended in 200 l of RIPA buffer (Sigma) according to manufacturer's protocol and supplemented with protease inhibitor cocktail (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…The coding region of mice Slc5a6 gene and ARPO, were PCR amplified using gene-specific primers (Table 1) for quantitative PCR study. Quantitative PCR conditions were same as described previously (44,47). The data were normalized to ARPO and then quantified by a relative relationship method (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using SLC19A2 and SLC19A3 knockout mouse models, we have also shown that both thiamin transporters 1 and 2 (THTR-1 and THTR-2) (products of the SLC19A2 and SLC19A3 genes, respectively) are involved in the vitaminuptake process (22). We showed that chronic alcohol exposure leads to a significant inhibition in thiamin uptake (25) and, on the basis of preliminary in vitro investigations with rat-derived pancreatic acinar AR42J cells, this effect appeared to be mediated at the level of transcription of the SLC19A2 and SLC19A3 genes (25). Our aims in this study were to confirm the involvement of transcriptional mechanisms in mediating the alcohol inhibitory effects on the SLC19A2 and SLC19A3 promoters in an in vivo setting and to delineate the molecular mechanisms involved in this inhibition.…”
mentioning
confidence: 88%
“…Transgenic mice carrying the full-length human SLC19A2 (Ϫ2,250 to Ϫ36) and SLC19A3 (Ϫ1,957 to ϩ59) promoters fused to the firefly luciferase reporter gene [previously generated and characterized by this laboratory (11,18)] were used (approval for their use was obtained from the Institutional Animal Care Use Committee of Long Beach VA Medical Center). Mice were fed the LieberDeCarli ethanol liquid diet (Dyets, Bethlehem, PA) [ethanol provided 25% of total ingested calories and was introduced gradually; calories were increased by 5% every day until we achieved 25% (8)] for 4 wk as described by us recently (25). Control littermates (sex-matched that had similar basal firefly luciferase mRNA expression) were pair fed with the same liquid diet but without ethanol (maltose-dextrin replaced ethanol isocalorically).…”
Section: Materials [mentioning
confidence: 99%